MicroRNA-33a functions as a bone metastasis suppressor in lung cancer by targeting parathyroid hormone related protein - Kuo, Po-Lin; Liao, Szi-Hui; Hung, Jen-Yu; Huang, Ming-Shyan; Hsu, Ya-Ling (Biochimica et biophysica acta, 2013)
Bone is a common site of metastasis for lung cancer, and is associated with significant morbidity and a dismal prognosis. MicroRNAs (miRNAs) are increasingly implicated in regulating the progression of malignancies. The efficacy of miR-33a or anti-miR-33a plasmid was assessed by Real-time PCR. Luciferase assays were using One-Glo Luciferase Assay System. Measurement of secreted factors was determined by ELISA kit. We have found that miR-33a, which is downregulated in lung cancer cells, directly targets PTHrP (parathyroid hormone-related protein), a potent stimulator of osteoclastic bone resorption, leading to decreased osteolytic bone metastasis. We also found that miR-33a levels are inversely correlated with PTHrP expression between human normal bronchial cell line and lung cancer cell lines. The reintroduction of miR-33a reduces the stimulatory effect of A549 on the production of osteoclastogenesis activator RANKL (receptor activator of nuclear factor kappa-B ligand) and M-CSF (macrophage colony-stimulating factor) on osteoblasts, while the expression of PTHrP is decreased in A549 cells. miR-33a overexpression also reduces the inhibitory activity of A549 on the production of OPG (osteoprotegerin), an osteoclastogenesis inhibitor. In addition, miR-33a-mediated PTHrP downregulation results in decreased IL-8 secretion in A549, which contributes to decreased lung cancer-mediated osteoclast differentiation and bone resorption. These findings have led us to conclude that miR-33a may be a potent tumor suppressor, which inhibits direct and indirect osteoclastogenesis through repression of PTHrP. miR-33a may even predict a poor prognosis for lung cancer patients. •miR-33a is downregulated in lung cancer cell lines.•miR-33a regulates the expression of PTHrP.•Overexpression of miR-33a decreases the induction of A549 on the production of RANKL and M-CSF in osteoblasts.•Ectopic expression of miR-33a decreases the stimulatory effect of A549 on osteoclastogenesis.•Knockdown of miR-33a triggers the inductive effect of BEAS-2B on the production of RANKL and M-CSF in osteoblasts.